Assessing channel change and bank stability downstream of a dam, Wyoming - Gilliam, Elizabeth Ann, author; Wohl, Ellen, advisor; Cenderelli, Dan, committee member; Bledsoe, Brian, committee member (Colorado State University. Libraries, 2011)
The Hog Park Creek watershed, in south-central Wyoming, has experienced several anthropogenic influences through time, the most notable in contemporary times being a reservoir in the upper extent of the watershed that was initially constructed in 1965 (Stage 1) and then later enlarged in 1985 (Stage 2). Flows released from the reservoir augment flows in Hog Park Creek. The existence of the channel-spanning dam creates a direct and identifiable disruption in the function of the two main drivers of geomorphic process: the water discharge, which has nearly doubled annually, and the concomitant disruption in the sediment transport regime. In order to assess channel responses, multiple analyses across a range of spatial and temporal scales were conducted. These include: a covariate hydrologic analysis relating three operational time periods using the Index of Hydrologic Alteration (IHA) software; an examination of the channel planform change from historical aerial photographs; analyses of annually repeated cross section survey data; and a study of bank erosion dynamics using the Bank Stability and Toe Erosion Model (BSTEM). The timing, magnitude and duration of flows have been altered since the Stage 1 implementation of the reservoir in 1965. Following a Stage 2 enlargement in 1985, the snowmelt-dominated hydrograph has most notably experienced a shift to bimodal high flows (an early spring, low-magnitude flow release from the reservoir and a late spring, high-magnitude flow release from the reservoir), a 550% increase in seasonal low flows, and a 10% reduction in peak discharges. The discharge historically corresponding to a 5-year recurrence interval now occurs annually under Stage 2 reservoir operations. Hence, formational flows for channel morphology have increased in both frequency and duration. The reduction in flow variability has ultimately altered the sediment transport regime, which is the base of the productivity and disturbance regimes that influence food web interactions, the composition of riparian vegetation and other ecological attributes of the pre-dam river ecosystem. Aerial photographic analysis of 29 years prior to and 36 years following the construction of the dam indicates an adjustment of channel width both temporally and spatially through the system. Statistical analyses suggest that the overall rate of change corresponds significantly to both location in the watershed (distance downstream of the reservoir) and the operation of the reservoir (volume, timing, and duration of water released). Most notably, the channel has shifted to a single-thread channel with reduced morphologic heterogeneity. Responses are most abrupt immediately downstream of the dam following its construction in 1965, whereas responses are more muted and delayed in the furthest downstream study reach. Cross section analyses indicate that each of the four study sites has experienced net erosion over the past five years. However, variation exists in erosion rates on the reach and site scales. Modeled erosion rates in BSTEM, corroborated with field data from bank erosion pins and repeated cross section surveys, suggest that the altered flow regime enhances bank erosion. The enhanced duration of high flows directly lead to increased amounts of toe scour. Flow regulation has changed the forces acting on the banks, including subsurface flow fluxes related to water level fluctuations and increased shear forces. This in turn has created hydraulic conditions that increase preferential erosion of the finer bank materials. However, this response is partially offset as channel geometry changes with width increase relative to depth, which alters the shear stress acting on the banks.
Keywords: dam; change; geomorphology; hydrology; Wyoming